Analisis Flypaper Effect Pengelolaan Keuangan Daerah di Kota Jayapura - Urip, Transna Putra; Indahyani, Rachmaeny (Jurnal Manajemen dan Bisnis, ISSN : 2615 - 0425 (Print), e-ISSN : 2622 - 7142 (Online))
This research generally have aims to analisys flypaper effect in Regional financial management on Jayapura City. More specific, the objectives are: (a) Flypaper Effect (b) efficiency in Regional financial managemen. Method will be used to analysis are: 1) Multiple regression, 2) analysis efficiency.The result this research are : 1)The fenomena flypaper in Regional Financial Management on Jayapura city is not founded, 2)Spend of money government at the health office especially for five groups expenditure show if the expenditure be used efficient.3) Spend of money govermen at the education office for five groups expenditure show if the expenditure be used inefficient.